Standar Operasional Prosedur (SOP) Berdasarkan Tipologi Sertifikasi Kompetensi Sumber Daya Manusia Lembaga Keuangan Mikro Syari’ah - Bambang Agus Sumantri (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2014)
Posts in this journal intended as a study and analysis regarding certification of competence standard typology of Human Resources Managers and employees as a form of profesioanalisme Islamic microfinance services management (BMT, BTM, and KJKS).